2017
DOI: 10.1002/app.45976
|View full text |Cite
|
Sign up to set email alerts
|

Low‐viscosity and soluble phthalonitrile resin with improved thermostability for organic wave‐transparent composites

Abstract: High processing viscosity and poor solubility limit the application of heterocyclic polymers for fabricating organic wavetransparent composites for aerospace applications. In this paper, a novel resin, poly(phthalazinone ether bisphenol fluorene) encapped with phthalonitrile (PPEBF-Ph), was synthesized and used as the matrix. Biphenol-based phthalonitrile monomer BP-Ph was also synthesized and blended with PPEBF-Ph to further lower the processing viscosity. Solubility tests showed that the resin was soluble in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…6,19 Furthermore, a solvent is not required during the cross-linking course of phthalonitrile, which enables the polymer to be free of voids and defects during the curing process. [20][21][22] In recent decades, researchers have emphasized the structural design of the phthalonitrile monomer to improve the comprehensive properties of resins. [23][24][25] It is generally well-known that the aromatic and/or heterocyclic structures endow the phthalonitriles with outstanding properties.…”
Section: Introductionmentioning
confidence: 99%
“…6,19 Furthermore, a solvent is not required during the cross-linking course of phthalonitrile, which enables the polymer to be free of voids and defects during the curing process. [20][21][22] In recent decades, researchers have emphasized the structural design of the phthalonitrile monomer to improve the comprehensive properties of resins. [23][24][25] It is generally well-known that the aromatic and/or heterocyclic structures endow the phthalonitriles with outstanding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high melting point and poor processability of the first generation of phthalonitrile monomers, flexible aromatic ether segments were introduced into the molecular structure of the monomers by Keller at Naval Laboratory (NRL) . At present, aliphatic aromatic ether, poly(ether imide), poly‐(arylene ether ketone), poly‐(arylene ether) and poly‐(arylene ether nitrile) have been reported. These monomers are usually prepared by the reaction of activated dihalogenated aromatic hydrocarbons and appropriate proportions of bisphenols to form phenolic intermediates, and then end‐capped with 4‐nitrophthalonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The phthalonitrile which had been cured at a high temperature can maintain good mechanical properties at 380-400 C and has better high-temperature resistance compared with traditional temperature-resistant resins such as poly (arylene ether nitrile)s, 6 polyimide, benzoxazine 7,8 , and bismaleimide. [9][10][11] However, when applied in high-temperature fields, such as aviation and aerospace, the thermostability of phthalonitrile still needs to be improved. A kind of dinitrile monomer, which contained silicon element with carbon-nitrogen bond in the middle, was synthesized through the reaction of dichlorosilane with amino phenoxy phthalonitrile by Zongbo Zhang et al 12 The results of thermogravimetric analysis (TGA) showed that the cured product had good properties.…”
Section: Introductionmentioning
confidence: 99%